Subclinical anaplasmosis infection on Ettawa Goats from Kaligesing, Purworejo, Central Java, Indonesia - Rosyadi, Imron; Nor Wijaya, Rendra; Ratna Nugraheni, Yudhi; Prastowo, Joko; Yanuartono; Argamjav, Bayanzul; Indarjulianto, Soedarmanto (Jurnal Ilmu Peternakan Terapan, 2024)
Small ruminant anaplasmosis is a blood-parasitic disease that can cause reproductive and economic problems, especially in Ettawa crossbred. In Indonesia, especially in Central Java Province, the study of this pathogen is still limited. This study examines subclinical anaplasmosis in Ettawa crossbred goats from central Java, Indonesia. Twenty adult goats underwent comprehensive physical and laboratory examinations. The physical exams assessed factors like sex, body temperature, heart rate, respiration, and rumen function. Laboratory testing involved blood smears to detect Anaplasmaspecies and complete blood counts using a hematology analyzer. The results showed that 8 goats were positive for Anaplasma, with 2 samples resembling A. phagocytophilum and 6 resembling A. marginale. Females were more likely to be infected. Infected goats did not exhibit significant changes in vital signs compared to healthy goats. However, infected goats had lower red blood cell counts, hemoglobin, and hematocrit, as well as higher white blood cell counts, indicating subclinical anemia. This is the first study to demonstrate the impact of subclinical Anaplasma infection on Ettawa crossbred goats in this region, highlighting the potential for production losses from this overlooked disease.